Fast Nurses' Response Time and Mild Family Anxiety in the Emergency Department of RSUD Undata Palu - Taqwin Taqwin; Astuti K. Datuamas; I Wayan Supetran; Ismunandar; Irsanty Collein; Dg. Mangemba; Nasrul Nasrul (Poltekkes Kemenkes Palu, 2026)
Background: Response time is an important indicator of emergency nursing service quality and may influence the anxiety level of patients' families. Delays in treatment can increase fear, uncertainty, and dissatisfaction among family members in emergencies. This study aimed to determine the relationship between nurses' response time and family anxiety levels in the Emergency Department of RSUD Undata Palu. Methods: This quantitative study used a correlational design with a cross-sectional approach. A total of 68 respondents were selected using consecutive sampling. Nurses' response time was measured using observation sheets and a stopwatch, while family anxiety levels were assessed using the Hamilton Anxiety Rating Scale (HARS). Data were analyzed using frequency distributions and Fisher's Exact Test, as several cells in the cross-tabulation had expected counts less than 5. Results: Most nurses' response times were categorized as fast (≤5 minutes), with 67 respondents (98.5%) and only 1 respondent (1.5%) experiencing a slow response time. Regarding anxiety levels, 46 respondents (67.6%) experienced mild anxiety and 22 respondents (32.4%) experienced severe anxiety. Fisher's Exact Test showed no statistically significant relationship between nurses' response time and family anxiety levels (p=0.324), although mild anxiety was more frequently observed among respondents who experienced fast response time. Conclusion: Nurses' response time in the Emergency Department of RSUD Undata Palu was generally fast, and most family members experienced mild anxiety. However, there was no statistically significant relationship between nurses' response time and family anxiety levels. These findings should be interpreted cautiously due to the highly unequal distribution of response time categories.